2020
DOI: 10.2147/cmar.s265803
|View full text |Cite
|
Sign up to set email alerts
|

<p>Baohuoside I via mTOR Apoptotic Signaling to Inhibit Glioma Cell Growth</p>

Abstract: Introduction Baohuoside I, a novel oncotherapeutic agent, has been reported to have anti-cancer effects on a variety of cancers, but its role in glioma and its molecular mechanism are still unclear. Methods The proliferation of U251 cells was detected by real-time cellular analysis (RTCA), CCK-8, Ki67 immunofluorescence and colony formation assay. The effect of Baohuoside I on the invasion and migration of U251 cells was measured by transwell and scratch tests. The apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…There is much evidence indicating that Icariside II exerts apoptosis-inducing effects in various cancer cell lines ( Table 1 ; Figure 2 ). After exposure to Icariside II, the expression of cleavage of caspase-3/8/9/7/PARP and Bax increases in concentration- and time-dependent manners, but the antiapoptotic factor BCL-2 was decreased in human liver cancer cell lines ( Guo et al, 2020a ). In prostate cancer, Icariside II was shown to activate caspase-3, promote cytochrome c release into cytosol, and simultaneously reduce the expression of the inactive, proenzymatic form of caspase-9 ( Lee et al, 2009 ).…”
Section: Toxicity and Pharmacokinetics Of Icariside IImentioning
confidence: 99%
See 3 more Smart Citations
“…There is much evidence indicating that Icariside II exerts apoptosis-inducing effects in various cancer cell lines ( Table 1 ; Figure 2 ). After exposure to Icariside II, the expression of cleavage of caspase-3/8/9/7/PARP and Bax increases in concentration- and time-dependent manners, but the antiapoptotic factor BCL-2 was decreased in human liver cancer cell lines ( Guo et al, 2020a ). In prostate cancer, Icariside II was shown to activate caspase-3, promote cytochrome c release into cytosol, and simultaneously reduce the expression of the inactive, proenzymatic form of caspase-9 ( Lee et al, 2009 ).…”
Section: Toxicity and Pharmacokinetics Of Icariside IImentioning
confidence: 99%
“…Accumulating evidence is indicating that Icariside II has the ability to control cancer cell invasion and migration in lung cancer ( Song et al, 2017 ), hepatocellular carcinoma ( Guo et al, 2020a ), cervical cancer ( Sun et al, 2020b ), osteosarcoma ( Choi et al, 2008 ), melanoma ( Peng and Zhang, 2018 ), and prostate cancer ( Li et al, 2020 ). In hepatocellular carcinoma ( Guo et al, 2020b ) and cervical cancer ( Sun et al, 2020a ), it has been demonstrated that Icariside II could weaken the migratory and invasive ability of HuH-7, HepG2, and HeLa cells through inhibiting metastasis-related protein MMP2/9 expression.…”
Section: Toxicity and Pharmacokinetics Of Icariside IImentioning
confidence: 99%
See 2 more Smart Citations